2021
DOI: 10.1016/j.heliyon.2021.e06676
|View full text |Cite
|
Sign up to set email alerts
|

Use of social networking in the Middle East: student perspectives in higher education

Abstract: This study aims to determine the benefits, risks, awareness, cultural factors, and sustainability, allied to social networking (SN) use in the higher education (HE) sector in Middle Eastern countries, namely Jordan, Saudi Arabia, and Turkey. Using an online survey, 1180 complete responses were collected and analyzed using the statistical confirmatory factor analysis method. The use of SN in the Middle Eastern HE sector has the capacity to promote and motivate students to acquire professional and personal skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 78 publications
(75 reference statements)
0
11
0
3
Order By: Relevance
“…Despite the complexity of preparing the instructional process by utilizing ICT, the material incorporated with various technologies contributes to many opportunities. In line with the research conducted by Issa et al (2021) revealed a better understanding of the benefits and risks, awareness, culture, and sustainability associated with the use of social networking (SN) in the higher education (HE) sector in the Middle East. In addition, another contribution is that the students may become selfdirected and very active -exploratory -learners in a short amount of time.…”
Section: Julietmentioning
confidence: 52%
“…Despite the complexity of preparing the instructional process by utilizing ICT, the material incorporated with various technologies contributes to many opportunities. In line with the research conducted by Issa et al (2021) revealed a better understanding of the benefits and risks, awareness, culture, and sustainability associated with the use of social networking (SN) in the higher education (HE) sector in the Middle East. In addition, another contribution is that the students may become selfdirected and very active -exploratory -learners in a short amount of time.…”
Section: Julietmentioning
confidence: 52%
“…El proceso de enseñanza-aprendizaje de la asignatura de Inglés, debe estar contemplado mediante el uso de Tecnologías de la Información y Comunicación (TICS), que aportan de forma significativa al aprendizaje conectivista y constructivista, promoviendo la implementación de recursos tecnológicos y direccionando nuevos ambientes de aprendizaje orientado al aprendizaje m-learning (Issa et al, 2021;Pinto-Almeida et al, 2022). No obstante, cambiar el paradigma pedagógico, es un nuevo reto que deben enfrentar tanto docentes como estudiantes, en la cual beneficiará mejorar el rendimiento académico (Muyulema-Allaica et al, 2021).…”
Section: Discussionunclassified
“…It's also important to provide suggestions to raise Jordanians' understanding of internet shopping's advantages. (Issa et al, 2021) reported that Jordan has 5.7 million social media users in January 2020. Online shops may create awareness about online purchasing and its restrictions by using social media.…”
Section: Culturementioning
confidence: 99%